Using Methylcellulose during Culturing and Cryopreservation of SPEV Passaged Culture - Koshchiy, S. V.; Vysekantsev, I. P.; Martsenyuk, V. F.; Petrenko, T. F.; Kudokotseva, E. V. (Problems of Cryobiology and Cryomedicine, 2008)
The possibility of adaptation of cultured embryonic pig kidney cells (SPEV) to growth in culturing medium 199+0.1% MC with reduced serum content to 1% has been shown. Cryoprotective properties of MC for the cryopreservation of SPEV have been determined.